The Destruction of ‘Mankind’ - Uljas, Sami (Zeitschrift für ägyptische Sprache und Altertumskunde, 2022)
The phonological changes undergone by the word rmṯ , ‘person’, are shown to have clashed with its emblematic and almost logographic written form established at the end of the Old Kingdom. The orthography of the lexeme was highly resistant to alterations in its phonology, which resulted in two changes of its gender over time, from original masculine to feminine, and finally back to masculine. However, Egyptian scribes sometimes tried to solve this discrepancy, and in one instance such attempts resulted in what in Egyptology has often been assumed to be a separate lexeme for ‘mankind’. It is argued here, however, that the said word never existed and that its alleged attestations exemplify one solution to the particular mismatches between traditional writing and spoken form of the word rmṯ .